Parametric Images in Assessing Bone Grafts Using Dynamic 18F-Fluoride PET. (22nd May 2011) - Wen, Lingfeng; Eberl, Stefan; Feng, (David) Dagan; Stalley, Paul; Huang, Gang; Fulham, Michael J.
Abstract : The early identification of graft failure would improve patient management. 18 F-fluoride is a suitable tracer for quantifying bone metabolism. Performance of parametric images constructed by Patlak graphical analysis (PGA) with various time periods was evaluated in the analysis of dynamic 18 F-fluoride PET studies of eight patients with fibula bone grafts after limb salvage surgery. The PGA parametric image approach tended to underestimate influx rate. The linear portion of PGA analysis was found to be from 10 to 50 min. It shows promise in providing a quantitative assessment of the viability of bone grafts.